Crosstalk between pluripotency factors and higher-order chromatin organization. (2nd September 2016) - Lopes Novo, Clara; Rugg-Gunn, Peter
ABSTRACT: Pluripotent cells are characterized by a globally open and accessible chromatin organization that is thought to contribute to cellular plasticity and developmental decision-making. We recently identified the pluripotency factor Nanog as a key regulator of this form of chromatin architecture in mouse embryonic stem cells. In particular, we demonstrated that the transcription factors Nanog and Sall1 co-dependently mediate the epigenetic state of pericentromeric heterochromatin to reinforce a more open and accessible organization in pluripotent cells. Here, we summarize our main findings and place the work into a broader context. We explore how heterochromatin domains could be targets of transcriptional networks in pluripotent cells and are coordinated with cell state. We propose this integration may be to balance the requirement for a dynamic and plastic chromatin organization in pluripotent cells, together with priming for a more restrictive nuclear compartmentalization that is triggered rapidly upon lineage commitment.